Application of E-Learning in Learning-Teaching Process for the Fourth year Students, English Program, Faculty of Education, Souphanouvong University - VANG , Khammee; LAMPHAIPHANH, Ketsalinh; PHAIQNAVONG, Somchay; CHIACHERLAO , Fongyarneng; ONSENGTAVANH, Fongmany (Souphanouvong University Journal Multidisciplinary Research and Development, 2020)
Application of E-Learning is a way of learning using the internet. The purposes of this study are (1) to provide an opportunity for both teachers and learners to assess the lesson content by using computers, smart phones through the internet, (2) to improve traditional learning-teaching so that this approach will become integrated through E-learning application and (3) to study E-learning satisfaction level in learning through the internet. The sample group of this study was 25 students who are studying English in year4. The sample group were specifically selected through Google classroom. Macro-media Authorware was used to create the lesson and the questionnaire was deployed as a study tool with Rating Scale and both Mean and Standard Deviation were also applied. The results of analysis found that : Students were able to assess their lessons, homework and class activities in any place and any time. To reduce their learning period, students could create some additional activities and learn other things, and the most important was that absent students could study what had been taught on their own time via the internet. The introduction of the E-learning system as an additional part to learning would have numerous advantages seeing that learners were able to further assess the lesson content and at the same time the teacher was able to effectively design learning using Multi-media, which could be done in the form of texts, visual aids, audio aids and videos. Learners were satisfied at the most average level and that meant E-learning application was the learning process using the internet really interested students to learn and they had better learning behaviors.